Porous chitosan particle, preparation method thereof and application of porous chitosan particle in wound healing
By preparing chitosan particles with specific molecular weight and deacetylation, the safety and effectiveness problems of existing hemostatic materials during use are solved, and efficient and safe hemostatic effect is achieved.
Patent Information
- Application Number
- CN202510162331.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-05-09
AI Technical Summary
There are safety and effectiveness issues in existing hemostatic materials during use. For example, QuickClot zeolite powder may cause burns in injured tissues, and protein hemostatic agents may cause biological contamination and reverse immune responses, and are expensive.
Porous chitosan particles are prepared by emulsification, cross-linking, pore making and freeze-drying, etc., to improve their porosity and hemagglutination index.
The prepared porous chitosan particles have high porosity and low hemocoagulation index, which significantly improves the specific surface area and fluid absorption rate of the hemostatic material, enhances the hemostatic effect, and reduces the risk of biocompatibility.
Smart Images

Figure CN119950797A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical supplies, and in particular to porous chitosan particles, a preparation method thereof and application thereof in wound healing. Background Art
[0002] Massive hemorrhage from trauma is the main cause of shock and death in the battlefield and violent conflicts. In pre-hospital situations such as battlefields, disasters and accidents, local hemostatic gauze combined with manual compression is the most common method of emergency hemostasis for trauma. Many effective local hemostatic agents, such as mineral-based (QuickClot zeolite powder), peptide-based and protein-based (thrombin, fibrin, gelatin and collagen), synthetic polymer-based (polycyanoacrylate, polyethylene glycol, polyvinyl alcohol), and polysaccharide-based (starch, chitosan, dextrose, oxidized cellulose) agents or materials have been used as hemostatic materials in the past 20 years. Hemostatic materials from various sources have their own advantages and disadvantages. For example, QuickClot zeolite powder is approved by the US Food and Drug Administration (FDA) for topical use in massive hemorrhage trauma, but it can cause severe burns to injured tissues due to hydrothermal hydration. Protein hemostatic agents have biological activity on the coagulation cascade and tissue regeneration, but may cause potential biological contamination and adverse immune reactions, are expensive, and their application scenarios are limited due to storage issues.
[0003] Chitosan is a natural polysaccharide with good compatibility, biological function and degradability. It is obtained by deacetylation of chitin and is one of the most promising hemostatic agents. This is mainly due to its high coagulation potential, abundant natural chitin, low cost, easy storage and long shelf life, biodegradability, antibacterial and promotion of tissue regeneration. Commercially available chitosan hemostatic agents include Celox gauze, dressing, HemCon TM Bandages have been widely used in battlefields and civilian emergency areas. The coagulation mechanism of chitosan hemostatic materials is the electrostatic interaction between positively charged chitosan and negatively charged red blood cells (RBC), as well as adhesion with platelets, aggregation to form platelet plugs, and the coagulation factors released by activated platelets to initiate the coagulation cascade reaction, produce fibrin, and then form a firm blood clot to block the bleeding point.
[0004] The preparation methods of porous chitosan include solvent pores, particle pores, gas pores and freeze drying. Solvent pores use inert solvents to form pores; particle pores create pores by adding particles; gas pores use supercritical gases or reaction-generated gases to create pores; freeze drying forms porous structures through ice crystal sublimation. These methods can adjust the pore size and porosity to meet different application requirements. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. The present invention provides a novel porous chitosan microparticle and a preparation method and application thereof. The provided porous chitosan hemostatic microparticle has high porosity and low blood coagulation index and can be used for wound healing and hemostasis.
[0006] Specifically, the present invention provides the following technical solutions:
[0007] In a first aspect of the present invention, a method for preparing porous chitosan particles is provided, comprising:
[0008] (1) providing a chitosan solution, wherein the chitosan solution is obtained by dissolving chitosan with a molecular weight of 10 kDa to 200 kDa and a deacetylation degree of 80% or more in an acetic acid solution;
[0009] (2) mixing the chitosan solution with an emulsifier and an oil phase, and performing emulsification treatment to obtain an emulsified product;
[0010] (3) mixing the emulsified product and an alkaline solution, and stirring until a product containing chitosan hydrogel microspheres is generated by reaction;
[0011] (4) washing the chitosan hydrogel microspheres with an organic solvent and deionized water, respectively, filtering, and freeze-drying to obtain porous chitosan microparticles.
[0012] The present invention provides a novel porous chitosan microparticle, which is obtained by emulsifying chitosan with a specific molecular weight and deacetylation degree in an oil phase, cross-linking and forming pores, and freeze-drying. The prepared porous chitosan hemostatic particles have a high porosity and a low blood coagulation index, and can be used for wound healing or wound hemostasis. According to a specific embodiment, the deacetylation degree of the chitosan is about 95%. The chitosan used can be from a variety of sources, including but not limited to shrimp, crab, crayfish, maggot shells or enoki mushrooms.
[0013] According to an embodiment of the present invention, the chitosan solution in step (1) is a 1wt% to 6wt% chitosan solution, and the chitosan solution is obtained by dissolving chitosan in a 0.5wt% to 3wt% acetic acid aqueous solution.
[0014] According to an embodiment of the present invention, the oil phase is selected from at least one of olive oil, soybean oil and liquid paraffin.
[0015] According to an embodiment of the present invention, the emulsifier is selected from at least one of Span 80, Span 60 and Tween 20.
[0016] According to an embodiment of the present invention, the emulsification process is performed at a rotation speed of 200-1000 rpm.
[0017] According to an embodiment of the present invention, the alkaline solution is selected from at least one of an ammonia-ammonium chloride buffer solution, a Tris-HCl buffer solution, a phosphate buffer solution, and a sodium carbonate-sodium bicarbonate buffer solution.
[0018] According to an embodiment of the present invention, the reaction time in step (3) is 0.5-2h; the volume ratio of the emulsified product to the alkaline solution is (5-30):1.
[0019] According to an embodiment of the present invention, the organic solvent in step (4) is ethyl acetate and ethanol.
[0020] The second aspect of the present invention provides a porous chitosan particle obtained according to the preparation method described in any embodiment of the first aspect; the porous chitosan particle has a porosity greater than 80% and a blood coagulation index less than 10.
[0021] The third aspect of the present invention provides use of the porous chitosan particles described in the second aspect in preparing a wound healing drug or a kit.
[0022] The beneficial effects achieved by the present invention are at least:
[0023] The porous chitosan hemostatic particles provided by the present invention are a kind of hemostatic agent that can be used for bleeding in complex surgical wounds such as gastrointestinal bleeding, solid organ bleeding, and large arterial and venous bleeding during surgery, or for bleeding in large arteries and veins of contaminated wounds during wartime and civilian emergencies. The main raw material is chitosan, which is abundant in source, safe and non-toxic. After the chitosan is emulsified, physically cross-linked to form pores, washed and dried, the surface is rough and porous, which significantly increases the specific surface area of the hemostatic material, increases the contact area between water molecules and the hemostatic material, and is beneficial for the hemostatic material to adsorb water molecules, thereby significantly increasing the ability of the hemostatic material to adsorb water molecules;
[0024] The physical cross-linking pore-making method is equivalent to the traditional chemical cross-linking in increasing the structural stability of polymer compounds, pore-making effects such as pore size, porosity, and channel structure stability, and the physical cross-linking pore-making method reduces the addition of toxic cross-linking agents, thereby improving the biocompatibility of porous chitosan particles. Using chitosan with different molecular weights and deacetylation degrees as raw materials, porous chitosan particles with different physical and chemical properties such as solubility, viscosity, charge, and charge can be prepared to meet the requirements of tissue adhesion, antibacterial properties, aggregation and adsorption of red blood cells, aggregation and activation of platelets, and other procoagulant and antibacterial effects in the process of hemostasis.
[0025] In addition, the hemostatic material of the present invention has a pore structure inside, which is conducive to the transfer of water molecules inside the hemostatic material, thereby enhancing the ability of the hemostatic material to transfer water molecules in the blood. Through the combined effect of these two aspects, its rapid liquid absorption performance is improved, and the coagulation components in the blood are concentrated during the hemostasis process, the coagulation process is accelerated, and effective physical hemostasis is performed. In addition, the porous chitosan hemostatic microparticles are positively charged under physiological conditions, and can interact with the electrostatics between negatively charged red blood cells (RBCs), and adhere to platelets to aggregate to form platelet plugs. The coagulation factors released by the activated platelets start the coagulation cascade reaction, produce fibrin, and then form a firm blood clot to block the bleeding point.
[0026] The porous chitosan microparticles with hemostatic and antibacterial functions provided by the present invention have good biocompatibility, no cytotoxicity, no sensitization reaction and acute toxicity, large specific surface area, fast liquid absorption rate, rapid swelling, and adjustable porous structure and protonation level under physiological conditions. It is a chitosan hemostatic material with great application prospects for clinical and on-site first aid. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Digital photos of the colonies in the negative control group in the antibacterial performance test of porous chitosan microparticles (No. 1 is Escherichia coli; No. 2 is Staphylococcus aureus)
[0028] Figure 2 Digital photos of colonies of each experimental group in the antibacterial performance test of porous chitosan particles (numbers 1 and 2 are digital photos of colonies of Escherichia coli and Staphylococcus aureus in Example 1; numbers 3 and 4 are digital photos of colonies of Escherichia coli and Staphylococcus aureus in Example 2; numbers 5 and 6 are digital photos of colonies of Escherichia coli and Staphylococcus aureus by Celox chitosan hemostatic powder)
[0029] Figure 3 The cytotoxicity bar graph of the porous chitosan microparticles prepared according to Examples 1 and 2 of the present invention. DETAILED DESCRIPTION
[0030] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0031] The present invention provides a method for preparing porous chitosan particles, comprising:
[0032] (1) providing a chitosan solution, wherein the chitosan solution is obtained by dissolving chitosan with a molecular weight of 10 kDa to 200 kDa and a deacetylation degree of 80% or more in an acetic acid solution;
[0033] (2) mixing the chitosan solution with an emulsifier and an oil phase, and performing emulsification treatment to obtain an emulsified product;
[0034] (3) mixing the emulsified product and an alkaline solution, and stirring until a product containing porous chitosan is generated by reaction;
[0035] (4) Washing the product containing porous chitosan with an organic solvent and deionized water respectively, filtering, and freeze-drying to obtain porous chitosan particles.
[0036] The preparation method of the porous chitosan hemostatic particles provided by the present invention is as follows: first, the raw chitosan is dissolved in an acetic acid solution of a certain concentration, and placed in a refrigerator at 4°C overnight until a clear and uniform chitosan solution is obtained. Then, the chitosan solution is slowly added to an emulsification system (oil phase: liquid paraffin, Span 80 as an emulsifier), mechanically stirred to form a uniform and stable oil-in-water emulsification system, and then an alkaline solution is added to the emulsification system, the chitosan molecules in the water phase of the oil-in-water system are deprotonated, the amino groups are physically cross-linked through hydrogen bonding, the chitosan in the water phase system is rapidly and irregularly phase-separated, and an uneven structure is formed on the surface, and after washing and drying, porous chitosan hemostatic particles with a microporous structure on the surface and inside of the particles are obtained.
[0037] By dissolving chitosan with different molecular weights and deacetylation degrees in an acetic acid system, the protonation level of the final product, porous chitosan hemostatic microparticles, under physiological conditions is regulated, thereby obtaining porous chitosan microparticles with ideal viscosity, antibacterial properties, solubility and biocompatibility under physiological conditions. Through emulsification, porous chitosan microparticles with a certain particle size and particle size distribution are formed to meet the requirements of rapid dispersion and quality control during the hemostasis process. Through cross-linking and pore formation, the surface and interior of the chitosan microparticles are given a porous structure, while increasing its stability, which is conducive to the formation of a firm blood clot during the hemostasis process.
[0038] The hemostatic material of the present invention is derived from chitosan, which is rich in hydrophilic hydroxyl and amino groups in its molecular structure. Its protonation degree under physiological conditions significantly affects its interaction with various cells and molecules in the body, thereby affecting its performance in the body. By controlling the chitosan raw materials and the degree of cross-linking in the process, the protonation degree of the porous chitosan hemostatic particles under physiological conditions can be regulated. The chitosan raw materials used include but are not limited to shrimp, crab, crayfish, maggot shells or Flammulina velutipes. According to a preferred embodiment, the molecular weight of the chitosan mentioned is 20kDa to 100kDa.
[0039] According to a specific embodiment, deionized water is used to prepare an acetic acid solution with a concentration of 0.5wt%-3wt%, and then a certain mass of raw chitosan powder with different molecular weights and deacetylation degrees is added to the acetic acid solution in batches, and placed in a 4°C refrigerator overnight to obtain a 1wt%-6wt% chitosan solution. According to a preferred embodiment, the deacetylation degree of the chitosan is at least 90%.
[0040] In the emulsification stage, the chitosan solution is first added to the emulsified system formed by evenly stirring the oil phase and the emulsifier, and emulsification is performed at a rotation speed of 200-1000 rpm to obtain an oil-in-water emulsion product.
[0041] After the emulsified product is prepared, 5 to 100 mL of alkaline solution is added to the emulsified product while the mechanical stirring speed remains unchanged, and the product is mechanically stirred to react for 0.5 h to 2 h to allow physical crosslinking to occur.
[0042] Then, an organic solvent is added to the above system to destroy the oil-in-water emulsion system to obtain a precipitate, which is then washed (for example, the precipitate can be washed three times with ethyl acetate and anhydrous ethanol respectively and filtered to obtain white particles), freeze-dried to obtain a white powder, sterilized with Co60, and sealed for later use, thereby obtaining the porous chitosan hemostatic particles of the present invention.
[0043] According to a specific embodiment, the oil phase includes but is not limited to one or more of olive oil, soybean oil, and liquid paraffin.
[0044] According to a specific embodiment, the emulsifier includes but is not limited to Span 80, Span 60, Tween 20, etc. According to a preferred embodiment, the emulsifier is Span 80.
[0045] According to a specific embodiment, the alkaline solution includes but is not limited to sodium hydroxide solution, ammonia-ammonium chloride buffer solution, Tris-HCl buffer solution, phosphate buffer solution, sodium carbonate-sodium bicarbonate buffer solution, etc. According to a preferred embodiment, the alkaline solution is sodium carbonate-sodium bicarbonate buffer solution or sodium hydroxide solution.
[0046] According to a specific embodiment, the volume ratio of the emulsified product and the alkaline solution is (5-30):1. The particle size distribution results show that the amount of alkali solution added has a significant effect on the particle size distribution of the porous chitosan microparticles, mainly because in the process of preparing the microparticles, an appropriate amount of alkali solution is added to the emulsified system, causing the protons of the amino groups in the chitosan polymer chain in the emulsified system to detach and form amino groups. The amino groups interact with each other and with other groups on the chitosan polymer chain through hydrogen bonds, thereby forming an orderly arranged chitosan microcrystalline structure. The microcrystalline structure serves as a physical cross-linking point to connect the chitosan polymer chain to form a chitosan microcrystalline physical cross-linking network, thereby causing the chitosan polymer to phase separate and precipitate. When the volume ratio of the emulsified system and the alkaline solution is relatively low, the degree of physical cross-linking of the chitosan polymer is low, and the degree of chitosan precipitation is low. In the subsequent preparation process, the oil-in-water emulsified system is broken, and the water phases merge with each other, resulting in a larger particle size of the prepared porous chitosan microparticles and a large particle size distribution range.
[0047] Herein, when indicating the particle size of porous chitosan microparticles, the d(0.1), d(0.5) and d(0.9) mentioned represent the particle size values corresponding to a certain percentage in the cumulative particle size distribution. Specifically: d(0.1) means that in the cumulative particle size distribution, particles with a particle size smaller than this value account for 10% of the total number of particles. In other words, 10% of the particles have a particle size less than or equal to d(0.1). d(0.5) is also called the median diameter or median particle size, which means that in the cumulative particle size distribution, particles with a particle size smaller than this value account for 50% of the total number of particles. In other words, half of the particles have a particle size less than or equal to d(0.5), and the other half are greater than or equal to d(0.5). d(0.9) means that in the cumulative particle size distribution, particles with a particle size smaller than this value account for 90% of the total number of particles. In other words, 90% of the particles have a particle size less than or equal to d(0.9).
[0048] According to a specific embodiment, when the average particle size of the prepared porous chitosan particles is 60-80 microns, the antibacterial effect of the porous chitosan particles is optimal.
[0049] The technical scheme of the present invention is described below by specific examples. It should be noted that these examples are only used to facilitate the understanding of those skilled in the art and should not be regarded as limiting the scope of protection of the present invention. Unless otherwise specified, the reagents used in the examples can be obtained commercially.
[0050] Example 1
[0051] Example 1 Porous chitosan particles were prepared by the following method, comprising:
[0052] (1) Preparation of chitosan solution
[0053] Use a measuring cylinder to accurately measure a certain amount of deionized water, and then add a certain amount of acetic acid to obtain a 1.5wt% acetic acid solution. Then, chitosan powder with a molecular weight of 20kDa and a deacetylation degree of 80% is added to the above acetic acid solution under magnetic stirring, and the mixture is allowed to stand in a refrigerator at 4°C overnight to obtain 100mL of a 4wt% chitosan solution.
[0054] (2) Emulsification, cross-linking, and pore formation
[0055] Take another three-necked flask, add an appropriate amount of olive oil, add the emulsifier Span 60 to the oil phase, stir mechanically for 5 minutes until the emulsifier and the oil phase are mixed, then slowly add the chitosan solution obtained in (1) to the emulsification system, and emulsify at a speed of 200 rpm. Then, add 5 mL of ammonia-ammonium chloride buffer solution with a pH of 9.0 to the emulsification system, stir continuously, and react for 0.5 hours.
[0056] (3) Washing and drying
[0057] Ethyl acetate was added to the above reaction system to destroy the emulsified system, and the precipitate was washed three times with ethyl acetate, anhydrous ethanol and deionized water respectively, filtered to obtain white particles, freeze-dried to obtain white powder, sterilized with Co60, sealed and stored for later use, to obtain porous chitosan particles.
[0058] Example 2
[0059] Example 2 Porous chitosan microparticles were prepared by the following method:
[0060] (1) Preparation of chitosan solution
[0061] Use a measuring cylinder to accurately measure a certain amount of deionized water, and then add a certain amount of acetic acid to obtain a 2wt% acetic acid solution. Then, chitosan powder with a molecular weight of 20 kDa and a deacetylation degree of 95% is added to the above acetic acid solution under magnetic stirring, and the mixture is allowed to stand in a refrigerator at 4°C overnight to obtain 100 mL of a 3wt% chitosan solution.
[0062] (2) Emulsification, cross-linking, and pore formation
[0063] Take another three-necked flask, add an appropriate amount of liquid paraffin, add the emulsifier Span 80 to the oil phase, stir mechanically for 5 minutes until the emulsifier and the oil phase are mixed, then slowly add the chitosan solution obtained in (1) to the emulsification system, and emulsify at a speed of 300 rpm. Then, add 30 mL of sodium carbonate-sodium bicarbonate buffer solution with a pH of 10.0 to the emulsification system, stir continuously, and react for 0.5 hours.
[0064] (3) Washing and drying
[0065] Ethyl acetate was added to the above reaction system to destroy the emulsified system, and the precipitate was washed three times with ethyl acetate, anhydrous ethanol and deionized water respectively, filtered to obtain white particles, freeze-dried to obtain white powder, sterilized with Co60, sealed and stored for later use, to obtain porous chitosan particles.
[0066] Example 3
[0067] Example 3 Porous chitosan microparticles were prepared by the following method:
[0068] (1) Preparation of chitosan solution
[0069] Use a measuring cylinder to accurately measure a certain amount of deionized water, and then add a certain amount of acetic acid to obtain a 2wt% acetic acid solution. Then, chitosan powder with a molecular weight of 80kDa and a deacetylation degree of 80% is added to the above acetic acid solution under magnetic stirring, and the mixture is allowed to stand in a refrigerator at 4°C overnight to obtain 100mL of a 3wt% chitosan solution.
[0070] (2) Emulsification, cross-linking, and pore formation
[0071] Take another three-necked flask, add an appropriate amount of soybean oil, add the emulsifier Tween 20 to the oil phase, stir mechanically for 5 minutes until the emulsifier and the oil phase are mixed, then slowly add the chitosan solution obtained in (1) to the emulsification system, and emulsify at a speed of 200 rpm. Then, add 50 mL of sodium hydroxide solution with a pH of 11.0 to the emulsification system, stir continuously, and react for 0.5 hours.
[0072] (3) Washing and drying
[0073] Ethyl acetate was added to the above reaction system to destroy the emulsified system, and the precipitate was washed three times with ethyl acetate, anhydrous ethanol and deionized water respectively, filtered to obtain white particles, freeze-dried to obtain white powder, sterilized with Co60, sealed and stored for later use, to obtain porous chitosan particles.
[0074] Example 4
[0075] Example 4 Porous chitosan microparticles were prepared by the following method:
[0076] (1) Preparation of chitosan solution
[0077] Use a measuring cylinder to accurately measure a certain amount of deionized water, and then add a certain amount of acetic acid to obtain a 2wt% acetic acid solution. Then, add chitosan powder with a molecular weight of 80kDa and a deacetylation degree of 95% to the above acetic acid solution under magnetic stirring, and let it stand in a refrigerator at 4°C overnight to obtain 100mL of a 3wt% chitosan solution.
[0078] (2) Emulsification, cross-linking, and pore formation
[0079] Take another three-necked flask, add an appropriate amount of olive oil, add the emulsifier Span 80 to the oil phase, stir mechanically for 5 minutes until the emulsifier and the oil phase are mixed, then slowly add the chitosan solution obtained in (1) to the emulsification system, and emulsify at a speed of 200 rpm. Then, add 50 mL of sodium hydroxide solution with a pH of 14.0 to the emulsification system, stir continuously, and react for 0.5 hours.
[0080] (3) Washing and drying
[0081] Ethyl acetate was added to the above reaction system to destroy the emulsified system, and the precipitate was washed three times with ethyl acetate, anhydrous ethanol and deionized water respectively, filtered to obtain white particles, freeze-dried to obtain white powder, sterilized with Co60, sealed and stored for later use, to obtain porous chitosan particles.
[0082] Example 5
[0083] Example 5 Porous chitosan microparticles were prepared by the following method:
[0084] (1) Preparation of chitosan solution
[0085] Use a measuring cylinder to accurately measure a certain amount of deionized water, and then add a certain amount of acetic acid to obtain a 1.5wt% acetic acid solution. Then, add chitosan powder with a molecular weight of 150kDa and a deacetylation degree of 80% to the above acetic acid solution under magnetic stirring, and let it stand in a refrigerator at 4°C overnight to obtain 100mL of a 2wt% chitosan solution.
[0086] (2) Emulsification, cross-linking, and pore formation
[0087] Take another three-necked flask, add an appropriate amount of liquid paraffin, add the emulsifier Span 60 to the oil phase, stir mechanically for 5 minutes until the emulsifier and the oil phase are mixed, then slowly add the chitosan solution obtained in (1) to the emulsification system, and emulsify at a speed of 200 rpm. Then, add 10 mL of sodium hydroxide solution with a pH of 14.0 to the emulsification system, stir continuously, and react for 0.5 hours.
[0088] (3) Washing and drying
[0089] Ethyl acetate was added to the above reaction system to destroy the emulsified system, and the precipitate was washed three times with ethyl acetate, anhydrous ethanol and deionized water respectively, filtered to obtain white particles, freeze-dried to obtain white powder, sterilized with Co60, sealed and stored for later use, to obtain porous chitosan particles.
[0090] Example 6
[0091] Example 6 Porous chitosan microparticles were prepared by the following method:
[0092] (1) Preparation of chitosan solution
[0093] Use a measuring cylinder to accurately measure a certain amount of deionized water, and then add a certain amount of acetic acid to obtain a 2wt% acetic acid solution. Then, chitosan powder with a molecular weight of 150kDa and a deacetylation degree of 95% is added to the above acetic acid solution under magnetic stirring, and the mixture is allowed to stand in a refrigerator at 4°C overnight to obtain 100mL of a 3wt% chitosan solution.
[0094] (2) Emulsification, cross-linking, and pore formation
[0095] Take another three-necked flask, add an appropriate amount of soybean oil, add the emulsifier Tween 20 to the oil phase, stir mechanically for 5 minutes until the emulsifier and the oil phase are mixed, then slowly add the chitosan solution obtained in (1) to the emulsification system, and emulsify at a speed of 200 rpm. Then, add 50 mL of phosphate buffer with a pH of 9.0 to the emulsification system, stir continuously, and react for 0.5 hours.
[0096] (3) Washing and drying
[0097] Ethyl acetate was added to the above reaction system to destroy the emulsified system, and the precipitate was washed three times with ethyl acetate, anhydrous ethanol and deionized water respectively, filtered to obtain white particles, freeze-dried to obtain white powder, sterilized with Co60, sealed and stored for later use, to obtain porous chitosan particles.
[0098] The porous chitosan particles prepared in Examples 1 to 6 above were characterized as follows:
[0099] Experiment 1 Determination of Zeta Potential
[0100] An appropriate amount of porous chitosan particles of each example was accurately weighed and fully dispersed in a PBS solution (pH=7.4), ultrasonically vibrated for 5 minutes, and allowed to stand for 30 minutes to stabilize. A MALVERN zetasizer nano zs instrument was used to start the test, and the average value of three measurements was taken.
[0101] Table 1 Zeta potential of porous chitosan particles in various examples
[0102] Example 1 Example 2 Example 3 Example 5 Zeta(mV) +29.35 +47.32 +34.76 +23.25
[0103] It can be seen from the Zeta potential results of the porous chitosan microparticles in each embodiment of Table 1 that the porous chitosan microparticles carry a positive charge in the PBS solution due to the presence of amino groups in the porous chitosan microparticles. The amount of charge of the porous chitosan hemostatic microparticles may be related to the molecular weight and deacetylation degree of the chitosan raw material used in its preparation process. Generally speaking, the lower the molecular weight and the higher the deacetylation degree, the higher the protonation level, the higher the charge, and the higher the corresponding procoagulant and antibacterial properties.
[0104] Experiment 2: Particle size distribution detection
[0105] 0.2 g of the porous chitosan particles of Examples 1-3 were taken and diluted and suspended in 200 mL of anhydrous ethanol to obtain sample solutions. The particle size distribution of the particles in the sample solutions was measured using a Malvern 2000 laser particle size analyzer. The results are shown in Table 2.
[0106] Table 2 Particle size distribution of porous chitosan particles in Examples 1-3
[0107]
[0108] From the particle size distribution results of the porous chitosan particles of Examples 1-3 in Table 2, it can be seen that the average particle size d(0.5) of Example 1 is the largest, and the particle size distribution range is relatively large, which is mainly related to the small volume of alkali added during its preparation process.
[0109] Experiment 3 Determination of the in vitro blood coagulation index of porous chitosan hemostatic microparticles
[0110] First, accurately weigh 0.2g of the porous chitosan hemostatic particles of each embodiment and put them into a plastic dish and preheat them at 37°C for 5min. 100μL of citric acid anticoagulated whole blood was added dropwise to the hemostat, and then 10μL of 0.2M CaCl2 solution was added, and the hemostat was incubated at 37°C for 5min. Then, 25mL of deionized water was added to the plastic dish and incubated with shaking at 37°C for 10min to rinse the uncoagulated blood on the hemostat. Finally, the absorbance of the uncoagulated blood solution was measured at 540nm (Abs1) using an ELISA reader (Varioskan LUX, ThermoFisher). The absorbance of 100μL of citric acid anticoagulated whole blood in 25mL of deionized water was used as a blank control (Abs0). The blood coagulation index (BCI) was calculated by the following formula.
[0111]
[0112] Table 3 Blood coagulation index (BCI) of porous chitosan microparticles in various examples
[0113] Example 1 Example 2 Example 3 Example 5 BCI 13.22 7.32 10.77 12.67
[0114] Table 3 shows the blood coagulation index of the porous chitosan particles prepared in each embodiment, taking Examples 1, 2, 3 and 5 as examples. It can be seen that the blood coagulation index of the porous chitosan particles in Example 2 is the lowest, and the blood clot formed by the reaction with anticoagulated whole blood is the strongest, which may be related to multiple factors such as its rough and porous surface structure and surface charge.
[0115] Experiment 4 Determination of antibacterial properties of porous chitosan hemostatic particles
[0116] The Gram-positive bacteria Staphylococcus aureus (S. aureus) and the Gram-negative bacteria Escherichia coli (E. coli) were used as model microorganisms. 100 μL of a 1×10 6 CFU / mL of bacterial liquid was inoculated into 0.2g of porous chitosan hemostatic particles of each embodiment and Celox chitosan hemostatic powder, and cultured at 37°C for 6h. After incubation, the sample was transferred to a centrifuge tube containing 1mL PBS, and then ultrasonically treated and vortexed for 10min to resuspend the adhered bacteria. The bacterial suspension was further diluted and spread on a 1.5% LB agar plate, and after the plate was incubated at 37°C for 24h, the microbial colonies formed were counted to calculate the antibacterial rate of each embodiment and Celox chitosan hemostatic powder.
[0117] Table 4 Antibacterial rate of each embodiment and Celox chitosan hemostatic powder
[0118] Example 1 Example 2 Celox Chitosan Hemostatic Powder Escherichia coli (%) 0.73 100 100 Staphylococcus aureus (%) 78.04 100 100
[0119] Taking the porous chitosan particles prepared in Example 2 as an example, the antibacterial rates of the porous chitosan particles against Escherichia coli and Staphylococcus aureus were tested. As shown in Table 4, the antibacterial rates of the porous chitosan particles in Example 2 against Escherichia coli and Staphylococcus aureus were both 100%, while the antibacterial rates of the porous chitosan particles in Example 1 against Escherichia coli were 0.73% and 78.04%, respectively, which may be related to the molecular weight and deacetylation degree of the chitosan raw materials used in its preparation process. For hemostatic materials, antibacterial properties are crucial, which can not only reduce the infection risk of bleeding wounds, but also promote wound healing. Figure 1 and Figure 2 These are digital photos of the colonies in the negative control group (without hemostatic powder and porous chitosan particles) and each experimental group.
[0120] Experiment 5 Cytotoxicity assay
[0121] The porous chitosan particles prepared in each embodiment were sterilized by irradiation with a cobalt source, and then immersed in RPMI 1640 culture medium (serum-free, purchased from Thermo Fisher Scientific, USA) at 37°C for 24 hours, and the supernatant was filtered to obtain the extract. L929 cells (mouse fibroblasts, from the National Laboratory Cell Resource Sharing Platform) were inoculated in a 96-well plate (the plate was pre-filled with complete culture medium containing RPMI 1640 culture medium and fetal bovine serum), with 5×10 4Then place the 96-well plate in an incubator at 37°C for 24h. Take out the 96-well plate, discard the old solution, add 100μL of the collected 100% concentration extract and 50% concentration extract to each well (50% concentration extract is obtained by mixing 100% concentration extract with an equal volume of RPMI1640 culture medium), and continue to place it in the incubator at 37°C for culture. Take it out after 48h, add 20μL of 5mg / ml MTT (thiazolyl blue, purchased from Beijing Jingke Hongda) aqueous solution to each well, and continue to place it in the incubator at 37°C for 4h. Finally, take out the 96-well plate, carefully discard the old solution, add 150μL of DMSO (dimethyl sulfoxide) to each well, shake for 10min, and place it in the microplate reader to read the OD value. The test wavelength is 570nm and the reference wavelength is 630nm. Six replicate wells were set for each sample, and blank culture medium (same steps as the experimental group, except that no hemostatic material was added) and 0.5wt% phenol aqueous solution were used as negative control group and positive control group, respectively. Relative growth rate (RGR%) was calculated as follows: RGR% = OD 样品 / OD 阴性对照 ×100%.
[0122] Depend on Figure 3 It can be seen that, referring to the negative control group, the relative cell proliferation rate of the porous chitosan particles prepared in Example 1 and Example 2 is greater than 100%, indicating that the porous chitosan particles prepared by the present invention have no cytotoxicity, and the prepared porous chitosan particles have a certain degree of cell proliferation promoting effect, which can promote wound healing to a certain extent.
[0123] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific implementation", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0124] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing porous chitosan microparticles, characterized in that: include: (1) providing a chitosan solution, wherein the chitosan solution is obtained by dissolving chitosan having a molecular weight of 10 kDa to 200 kDa and a deacetylation degree of at least 80% in an acetic acid solution; (2) mixing the chitosan solution with an emulsifier and an oil phase, and performing emulsification treatment to obtain an emulsified product; (3) mixing the emulsified product and an alkaline solution, and stirring until a product containing chitosan hydrogel microspheres is generated by reaction; (4) washing the chitosan hydrogel microspheres with an organic solvent and deionized water, respectively, filtering, and freeze-drying to obtain porous chitosan microparticles.
2. The method for preparing porous chitosan microparticles according to claim 1, characterized in that: The chitosan solution in step (1) is a 1wt% to 6wt% chitosan solution, which is obtained by dissolving chitosan in a 0.5wt% to 3wt% acetic acid aqueous solution.
3. The method for preparing porous chitosan microparticles according to claim 1, characterized in that: The oil phase is selected from at least one of olive oil, soybean oil and liquid paraffin.
4. The method for preparing porous chitosan microparticles according to claim 1, characterized in that: The emulsifier is selected from at least one of Span 80, Span 60 and Tween 20.
5. The method for preparing porous chitosan microparticles according to claim 1, characterized in that: The emulsification process is carried out at a rotation speed of 200-1000 rpm.
6. The method for preparing porous chitosan microparticles according to claim 1, characterized in that: The alkaline solution is selected from at least one of ammonia-ammonium chloride buffer solution, Tris-HCl buffer solution, phosphate buffer solution, and sodium carbonate-sodium bicarbonate buffer solution.
7. The method for preparing porous chitosan microparticles according to claim 1, characterized in that: The reaction time in step (3) is 0.5-2h; the volume ratio of the emulsified product to the alkaline solution is (5-30):
1.
8. The method for preparing porous chitosan microparticles according to claim 1, characterized in that: The organic solvent in step (4) is ethyl acetate and ethanol.
9. A porous chitosan particle, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 8; the porosity of the porous chitosan particles is greater than 80% and the blood coagulation index is less than 10.
10. Use of the porous chitosan microparticles according to claim 9 in preparing a wound healing medicine or a kit.
Citation Information
Cited By
Chitosan immobilized MOF808 particles and preparation method thereof
CN121971649A